Ecocriticism, Geophilosophy, and the [Truth] of Ecology - Dixon, Peter (Université d'Ottawa / University of Ottawa, 2011)
This thesis addresses the question posed to ecocriticism by Dana Phillips in his iconoclastic The Truth of Ecology: Nature, Culture, and Literature in America: “What is the truth of ecology, insofar as this truth is addressed by literature and art?” by examining how ecocriticism has, or has failed to, contextualize ecocritical discourse within an ecological framework. After reviewing the current state of ecocriticism and its relationship with environmentalism, the thesis suggests that both rely on the same outmoded, inaccurate and essentially inutile ecological concepts and language, and argues for a new approach to ecocriticism that borrows its concepts and language from the geophilosophy of Gilles Deleuze and Felix Guattari. The thesis concludes with a reassessment of the work of Barry Lopez, showing how his fiction, when viewed through the lens of geophilosophy, does not support essentialist notions of nature, but rather works to articulate a world of multiplicities, and new modes of becoming.
Keywords: ecocriticism; Gilles Deleuze; Felix Guattari; geophilosophy; ecology; Barry Lopez